Drought Status and its Management from the Viewpoint of Professionals and Households’ Heads in Rural Areas of EslamabadGharb, Iran - bahman shafiei; Hamid Barghi; Yusef Ghanbari (تحقيقات جغرافيايی, 2019)
Aims & Backgrounds: Climate change, the quantitative and qualitative decline of water resources and the increasing trend of the worldchr('39')s population have made water management difficult. The purpose of this study was to assess the situation and management of meteorological and agricultural droughts from the point of view of experts and household supervisors in rural areas of Eslamabad Gharb. Methodology: This descriptive-analytical study was conducted in 2017 in 7 households of Eslamabad Gharb. A total of 374 households (in 21 villages) were selected through multi-stage stratified random sampling. Data were collected through library and field research (questionnaire and interview). To analyze the quantitative data, standardized precipitation indices, standardized transpiration and one-sample T-test, and in the qualitative part, Delphi method was used.. Findings: According to the results of the Standardized Precipitation Index, from 1986 to 2016, 14 years of drought occurred at the county level (8 years normal, 4 years moderate and 2 years severe). According to the results of the long-term standardized transpiration index, 2.1% of the city population was affected by moderate drought in 2008-2009, and 64.6% by mild drought. Conclusion: Rural participation in drought management planning is the most important and effective factor affecting drought management.